2020
DOI: 10.1097/brs.0000000000003604
|View full text |Cite|
|
Sign up to set email alerts
|

Preoperative Parameters for Predicting the Loss of Lordosis After Cervical Laminoplasty

Abstract: Study Design. Retrospective study. Objective. The preoperative parameters for predicting the loss of lordosis after cervical laminoplasty were investigated in the present study. Summary of Background Data. Cervical laminoplasty is an effective surgical method to decompress the cervical spinal cord. Maintaining cervical lordosis after laminoplasty is an important factor to ensure the successful surgical treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Kim et al (2020) in their retrospective study attempted to recognize predisposing factors of loss of cervical lordosis in 106 patients that underwent a cervical laminoplasty procedure [ 26 ]. Authors divided their patients in 38 that preserved cervical lordosis and in 68 patients that lost cervical lordosis.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2020) in their retrospective study attempted to recognize predisposing factors of loss of cervical lordosis in 106 patients that underwent a cervical laminoplasty procedure [ 26 ]. Authors divided their patients in 38 that preserved cervical lordosis and in 68 patients that lost cervical lordosis.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, preoperative cross-sectional area and fatty degeneration of paraspinal muscle were correlated with loss of lordosis in laminoplasty [ 14 , 20 ]. Cervical paraspinal extensor muscles have been shown to contribute to maintaining cervical spine stability [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative cervical sagittal alignment is affected by many factors, such as the type of implant system, distraction degree, intraoperative procedure, and paraspinal muscle status [ 11 14 ]. Theoretically, to maintain a forward gaze position, the posterior extensor muscles of the neck need to be contracted [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of cervical kyphosis leads to increasing the length and decreasing the CSA of the neck extensors. Studies found that cervical lordosis was correlated with fat infiltration of deep neck extensors (multifidus, spinalis cervicis, and capitis) at the C4/5 and C7/T1 segments [ 62 ] but not at C5/6 [ 63 ]. Xing-Jin Wang et al [ 64 ] found no differences in cervical lordosis angle in patients with more extensor muscle fat infiltration.…”
Section: Strengths and Limitationsmentioning
confidence: 99%